Drawn and Dangerous : Italian Comics of the 1970s and 1980s - Castaldi, Simone (Book collections on Project MUSE., 2010)
Exploring an overlooked era of Italian history roiled by domestic terrorism, political assassination, and student protests, this book shines a new light on what was a dark decade, but an unexpectedly prolific and innovative period among artists of comics intended for adults. Blurring the lines between high art and popular consumption, artists of the Italian comics scene went beyond passively documenting history and began actively shaping it through the creation of fictional worlds where history, cultural data, and pop-realism interacted freely.